CRIMINAL JUSTICE SYSTEM - Muhadar (Awang Long Law Review, 2018)
CJS, the have lavel is police investigation, he was prosecuted/ajudications and correctional institution. Zelznijk and Nonetz the three level is Criminal Justice System, Pra adjudication, adjudication and post adjudication. There is KPK in investigation corruption criminal, overstate/increase Justice War.